Forecasting Climate Variability in Nepal - Raghu Bir Bista (PT Mattawang Mediatama Solution, 2023)
Climate variability is noted a critical issue in Nepal. This paper investigates empirically and analytically whether climate variability exists or not in different altitudes, whether its direction moves and what will be its future direction. In this study, we used a time series forecasting model based on the secondary data of hydrology and metrology collected from the Department of Hydrology and Metrology, the Government of Nepal. As a result, this paper found climate variability in the different parts of Nepal where variations of climatic variables (temperature and rainfall precipitation) are found all months of the year. In the estimation, on average temperature rising per annum is by 20 C from 1975 to 2012. However, declining rainfall per annum was noticed. Additionally, the estimated forecasting of temperature variation over the next 40 years would be 60c over. In the case of rainfall forecast, it would be constant and results from drought at high altitude and flood at low altitude. Therefore, climate variability may be a big threat in the next 40 years across the country, of Nepal. The result may be valuable input to the policymakers and farmers for economics as usual.